Immunomodulation with SA-FasL-Engineered Microgels Achieves Long-Term Survival of Allogeneic Islet Grafts. (July 2018) - Woodward, Kyle B; Headen, Devon M; Shrestha, Pradeep; Tan, Min; Bowen, William S; Coronel, María M; Hunckler, Michael D; Weaver, Jessica D; Yolcu, Esma S; García, Andrés J; Shirwan, Haval
Abstract : Introduction and Objective: Allogenic islet transplantation has shown efficacy in the clinic for the treatment of type 1 diabetes. However, sustained survival of allogeneic islet grafts requires chronic immunosuppression that has significant adverse effects. T effector (Teff) cells recognizing and responding to allograft antigens are the major culprit of graft rejection. Upon activation, Teff cells upregulate Fas death receptor on their surface and become sensitive to FasL-mediated apoptosis. Fas pathway, therefore, presents an important target for immunomodulation to block alloreactive responses with significant therapeutic potential. Herein, we assessed the efficacy of PEG microgels engineered with a novel form of FasL chimeric with a modified form of core streptavidin, SA-FasL, in achieving sustained survival of allogeneic islet grafts in the absence of chronic immunosuppression. Materials and Methods: Microgels presenting biotin on their surface were produced by reacting biotin-PEG-thiol with a maleimide-terminated 4-arm poly(ethylene) glycol macromer, and generating 200 μm diameter microgels crosslinked with dithiothreitol. Biotinylated microgels were engineered with SA-FasL (1 μg/10 3 microgels) taking the advantage of the high affinity interaction between biotin and streptavidin. The apoptotic activity of SA-FasL-engineered microgels was tested on mouse A20 B cell lymphocytes in vitro . The immunomodulatory function of microgels for the prevention of graft rejection was tested by mixing 500 BALB/c naïve islets with 1000 SA-FasL-engineered microgels and transplanting under the kidney capsule of streptozotocin-induced diabetic C57BL/6 recipients. A group of recipients were also treated transiently with rapamycin (0.2 mg/kg daily for 15 days starting the day of transplantation). Results and Discussion: Biotin-PEG microgels were efficiently coupled with SA-FasL, and showed a dose-dependent apoptotic activity in A20 cells. Co-transplantation of SA-FasL-engineered microgels with naïve islets led to prolonged survival of grafts as compared with the control group (islets + unmodified microgels) with 20% surviving for a 200-day observation period. Transient use of low dose rapamycin, enhanced survival to > 90% of the grafts. In marked contrast, only 20% of islets co-transplanted with PEG microgels, and short-course rapamycin, survived long-term. Importantly, CD4 + CD25 + FoxP3 + Treg cells were required for graft survival as depletion of this cell population on day 50 post-transplantation resulted in prompt rejection. Conclusion: These results provide strong proof-of-efficacy and feasibility for the use of SA-FasL-engineered microgels as an off-the-shelf product for the modulation of alloreactive responses with significant therapeutic potential. Funded in part by NIH (grants R21EB020107, R21AI113348, 185 R56AI121281, and F30AR069472) and the Juvenile Diabetes Research Foundation (2-SRA-186 2014-287-Q-R).